2006
DOI: 10.1073/pnas.0602952103
|View full text |Cite
|
Sign up to set email alerts
|

Templated biomineralization on self-assembled protein fibers

Abstract: Biological mineralization of tissues in living organisms relies on proteins that preferentially nucleate minerals and control their growth. This process is often referred to as ''templating,'' but this term has become generic, denoting various proposed mineralorganic interactions including both chemical and structural affinities. Here, we present an approach using self-assembled networks of elastin and fibronectin fibers, similar to the extracellular matrix. When induced onto negatively charged sulfonated poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
56
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 27 publications
0
56
0
Order By: Relevance
“…[1] Hydroxyapatite (HA), Ca 5 (PO 4 ) 3 (OH) is a polymorph of calcium phosphate Ca 3 (PO 4 ) 2 in which two hydroxyl ligands have been substituted for phosphate groups. Hydroxyapatite is the primary inorganic component of both teeth and bone, each of which possess subtle microstructure differences that account for the significant variations in mechanical properties.…”
mentioning
confidence: 99%
“…[1] Hydroxyapatite (HA), Ca 5 (PO 4 ) 3 (OH) is a polymorph of calcium phosphate Ca 3 (PO 4 ) 2 in which two hydroxyl ligands have been substituted for phosphate groups. Hydroxyapatite is the primary inorganic component of both teeth and bone, each of which possess subtle microstructure differences that account for the significant variations in mechanical properties.…”
mentioning
confidence: 99%
“…Calcite microcrystals have been grown on a wide variety of templates, including Kevlar, [54][55][56] nylon, [57] self-assembled monolayers, proteins, etc. [51,[58][59][60][61][62][63][64][65][66][67][68] Reminiscent of collagen processing, [69] the approach delineated herein represents an example of hierarchical self-assembly in which each stage involves building blocks of increasing size such that the resulting supramolecular structure spans over six orders of magnitude, from nanometer-sized covalent building blocks to millimeter calcite wires. [70] We have demonstrated that streptavidin (the linker) combined with a linear tetrabiotinylated connector, the [Fe(Biot 2 -terpy) 2 ] 2+ complex, spontaneously self-assemble into a one-dimensional metal-organic protein framework.…”
mentioning
confidence: 99%
“…Their high surface energies enable ready assembly with organic molecules (15). Such organic termination or capping may mask the original NP surface identity (4) (hydrophobicity, charge, and/or chemical group), resulting in a modified outer shell, which may feature unique configuration and functionality (electronic, optical, steric, and/or chemical) (1,5,16). However, a clear understanding of the organic ligand-NP interactions and surface chemistry-structure relations is still far from complete.…”
mentioning
confidence: 99%